Analisis Faktor – Faktor Yang Mempengaruhi Turnover Intension Karyawan Pada PT. Mitra Beton Mandiri Proyek Bendungan Tigadihaji – Oku Selatan - Aulia Rahmi, Neneng; Mardiah Kenamon; Rosmala Dewi (Jurnal Bisnis Darmajaya, 2024)
This study discusses the effect of workload and compensation on employee turnover intention at PT. Mitra Beton Mandiri Tigadihaji Dam Project - South OKU. The population in this study were 30 employees of PT. Mitra Beton Mandiri. The analytilcal method used was quantitative method using Multiple Linear Regression analysis tool. The results of the t-test analysis of the workload variable (X1) are 2.956, which is greater than the t table of 2.05183, stated that the variable (X1) has a significant effect on employee turnover intention at PT. Mitra Beton Mandiri, while the t-test of the compensation variable (X2) is -1.694, which is smaller than the t table of 2.956, stated that the compensation variable (X2) does not have a significant effect on employee turnover intention at PT. Mitra Beton Mandiri. The calculate F value 6,096 was greater than F Table of 3,35 stated that together workload and compensation has sifnificant influence on turnover intention at PT. Mitra Beton Mandiri Tigadihaji Dam Project - South OKU. Ther valuer of ther coerffircirernt of derterrmirnatiron (R Squarer) of 0.311 meran that irn thirs caser ther contrirbutiron of ther irnfluerncer of Workload and Compernsatiron on Ermployerers' Turnoverr Irnternsiron irs 31,1%, whirler ther rermairnirng 68,8% was irnfluerncerd by otherr varirablers erxcluderd irn thirls rerserarch moderl such a work ernvirronmernt, leraderrshirp styler, and organirzatironal culturer.